Pembangunan Sistem Informasi Perpustakaan Berbasis Web menggunakan Metode Rapid Application Development (RAD) (Studi pada : SMK Negeri 11 Malang) - Nur Aini; Satrio Agung Wicaksono; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The library which is located at SMK Negeri 11 Malang based on the observation results is still manual in providing services to library visitors who borrow books by writing a note book. Therefore a study entitled